Ultrafast Gyroscopic Measurements in a Passive All‐Fiber Mach–Zehnder Interferometer via Time‐Stretch Technique. Issue 8 (3rd August 2022) - Kudelin, Igor; Sugavanam, Srikanth; Chernysheva, Maria
Abstract : Interferometric Fiber‐Optic Gyroscopes Optical measurements of rotation velocities traditionally rely on highly averaged Sagnac effect interrogation. In manuscript number 2200092, Igor Kudelin, Srikanth Sugavanam, and Maria Chernysheva enhance the possibilities of direct rotation detection by combining the benefits of the Mach‐Zehnder interferometer and dispersive Fourier transform measurement technique. Such an approach allows achieving a new level of angular rotation resolution as low as 0.33 mdeg s −1 at unprecedent acquisition rates beyond tens of MHz.